2022
DOI: 10.1007/s12609-022-00468-w
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Disparities and the Digital Divide

Abstract: Purpose of Review Socioeconomically disadvantaged populations and minority groups suffer from high breast cancer mortality, a disparity caused by decreased access to specialty care, lower treatment adherence, co-morbidities, and genetic predisposition for biologically aggressive breast tumor subtypes. Telehealth has the potential to mitigate breast cancer disparities by increasing access to specialty care and health information. However, unequal access to high-speed/broadband internet service and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Similarly, about 34% of those who have an annual household income less than $30,000 experienced difficulties in paying for high-speed internet services [38]. Hence, it will be important to assess patients' accessibility and ability to use digital technology and develop a best practice to leverage telehealth among underserved populations [39]. Providing patient-level training, ways to engage others (e.g., family) when assisting patients, and technical support are areas needed to ensure the equity in telehealth services [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, about 34% of those who have an annual household income less than $30,000 experienced difficulties in paying for high-speed internet services [38]. Hence, it will be important to assess patients' accessibility and ability to use digital technology and develop a best practice to leverage telehealth among underserved populations [39]. Providing patient-level training, ways to engage others (e.g., family) when assisting patients, and technical support are areas needed to ensure the equity in telehealth services [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the prevalence of low health literacy increases with the number of chronic conditions, rising from 10.6% among those with no chronic conditions to 24.7% among those with 3 or more. 86 Additionally, in this electronic age, limited digital literacy has driven the formation of “the Digital Divide,” 87 , 88 , 89 , 90 particularly affecting underserved communities.…”
Section: Patient and Clinician Awareness Of The Overlap Between Cardi...mentioning
confidence: 99%
“…Despite these advances in methodology, the datasets available initially were only applicable to the state of Indiana, making its application limited. Addressing these shortcomings, our group developed the Digital Inequity Index (DII) that utilized similar methodologies and data sources of the Digital Divide Index while expanding the coverage to the entirety of the United States at the county level [50 ▪ ].While many recent works on digital inequity have encompassed literature reviews and small-scaled implementation studies on diseases such as breast cancer, brain tumors, and COVID-19 [51 ▪▪ ,52 ▪▪ ,53–57], modern large-data analyses on digital inequity have only been performed on cancers of the esophagus and gastrointestinal system by our group [50 ▪ ]. In short, this study observed that, after adjusting for the impact of traditional SDoH, such as education level, income, disability status, and others, poorer digital resource access contributed to upwards of 20% differences in postoperative surveillance and 16% differences in survival time for patients diagnosed with esophageal and other types of gastrointestinal malignancies.…”
Section: Text Of Reviewmentioning
confidence: 99%